PROJECT-BASED LEARNING TO IMPROVE STUDENTS’ SKILLS IN ANALYZING AND DESIGNING VISUAL LITERACY MODEL - Nopita Trihastutie (Widya Mandala Surabaya Catholic University, 2025)
This current research aims to analyze how Project-Based Learning (PBL) improves students’ skills in analyzing and designing literacy models that support intercultural communication. It employed a descriptive qualitative approach, which integrated observation method and content analysis. In this current research, a combined method reconciles an axiological-oriented observation method with an ontological-oriented content analysis method (visual media product and result report). This approach focuses on acceptance, anticipation, dialogical exchanges, and dialectical diversity in the investigation. The findings show that PBL supports students’ abilities for distinguishing, organizing, attribution, inventory, ideation, and visual creativity. In conclusion, PBL enhances students' abilities to analyze and develop literacy models that facilitate intercultural communication by creating opportunity to connect concepts with the reality, participating in field research, fostering soft skill and hard skill, integrating knowledge from various disciplines.